Toxoplasma gondii seropositivity and serointensity and cognitive function in adults - Gale, Shawn D.; Erickson, Lance D.; Thacker, Evan L.; Mitchell, Elizabeth L.; Brown, Bruce L.; Hedges, Dawson W. (PLOS Neglected Tropical Diseases, 2020)
Author summary Toxoplasma gondii is a parasite that reproduces in cats but that can infect other animals and humans. Toxoplasma gondii has an affinity for the brain and infection results in a long-term immune response that may have negative effects. Animal models have shown that Toxoplasma gondii can affect behavior and cognition (thinking). In humans, the association is less clear, but there are associations between infection and variety of psychiatric and neurological conditions such as schizophrenia and epilepsy. Toxoplasma gondii may even increase the risk of dementia. If true, it is possible that the presence of this infection may affect thinking long before the onset of dementia. We sought to determine if the presence of antibodies in the blood to Toxoplasma gondii, which is the immune system’s response to past infections, might be associated with performance on measures of cognition. We analyzed a large dataset, the UK Biobank, which includes measures of cognition and blood test results for antibodies to Toxoplasma gondii. We found that both the presence of antibodies as well as the amount of these antibodies were related to some aspects of cognition, particularly problem solving and reasoning in otherwise healthy adults ages 40 to 69 years.